High gain antenna at 915 MHz for off grid wireless networks - Hussam Hamid Keriee; Mohamad Kamal A. Rahim; Nawres Abbas Nayyef; Zahriladha Zakaria; Ahmed Jamal Abdullah Al- Gburi; Fahad Taha Al-Dhief; Mustafa M. Jawad (Institute of Advanced Engineering and Science, 2020)
This paper presents a high gain antenna for off-grid wireless networks at 915 MHz. The requirements for compact size and high gain antenna are needed in the industrial, scientific and medical (ISM) band for better performance and coverage. Hence, microstrip planar substrate is proposed to overcome the size challenges. The proposed antenna is designed based on rectangular patch with air gap technique. The proposed antenna is optimized using computer simulation technology software (CST) and fabricated on low profile FR-4 substrate. The measured performance agreed well with the simulated one. The reflection of less than -10 dB is obtained with high gain of 6.928 dB at desired frequency. Overall, this antenna can be a good candidate for the off-grid wireless network applications.